Idiopathic spinal accessory nerve injury - Pereira, Pedro Cubelo; de Aguiar, Benedita Bianchi; Dantas, Duarte; Vaz, Inês Machado (BIRTH AND GROWTH MEDICAL JOURNAL, 2020)
Palsy of the eleventh cranial nerve – or spinal accessory nerve (SAN) − is a rare cause of scapular winging, leading to painful upper extremity disability due to weakness and atrophy of the trapezius muscle. Most SAN injuries are iatrogenic, and no specific pediatric epidemiology is known. Herein is described the case of a 17-year-old adolescent referred to Physical and Rehabilitation Medicine consultation due to insidious right shoulder pain with two years of evolution. Shoulder pain combined with muscular atrophy is suggestive of nerve lesion. Electromyography is the gold standard exam and showed segmental demyelination and axonotmesis in this case. After evaluation, the patient underwent physiotherapy, with excellent results. In conclusion, SAN injury treatment can be conservative or surgical and physiotherapy is the basis of early treatment in most cases. Recovery can occur even after a significant period of time.